ANALYZING THE RELATIONSHIP BETWEEN TRADE OPENNESS AND ECONOMIC GROWTH IN NORTH MACEDONIA: A SVAR APPROACH - Katerina Shapkova Kocevska; Elena Makrevska Disoska; Jasna Tonovska (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu)
The relationship between trade openness and economic growth is complex. We employ a structural vector auto-regression (SVAR) model using quarterly data for the period from 2005 to 2022 to estimate the impact of trade openness on the economic growth in North Macedonia. The study's findings indicate a negative and significant relationship between trade openness and economic development in the short and long run. The complexity of this relationship highlights an adverse impact on countries specialising in low-quality production or those with low levels of human capital accumulation, such as North Macedonia. The dynamic effects of shocks to trade openness on interest rates, consumer price index, interest rates, labour force, and exchange rate are investigated using impulse response functions. The paper suggests that North Macedonia's trade strategy requires reorientation towards trade diversification, attracting export-oriented FDIs, and fostering regional trade integration to achieve sustainable economic growth and development.